2005
DOI: 10.1194/jlr.m500143-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular trafficking of vitamin E in hepatocytes: the role of tocopherol transfer protein

Abstract: The term vitamin E denotes a family of tocopherols and tocotrienols, plant lipids that are essential for vertebrate fertility and health. The principal form of vitamin E found in humans, RRR -␣ -tocopherol (TOH), is thought to protect cells by virtue of its ability to quench free radicals, and functions as the main lipid-soluble antioxidant. Regulation of vitamin E homeostasis occurs in the liver, where TOH is selectively retained while other forms of vitamin E are degraded. Through the action of tocopherol tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(155 citation statements)
references
References 56 publications
(70 reference statements)
8
145
0
Order By: Relevance
“…As shown in Fig. 3A , NBD-tocopherol was efficiently taken up by the cells and concentrated in a vesicular, perinuclear compartment, reminiscent of our previous observations in human HepG2 and rat McARH-7777 hepatocytes ( 35,54 ). We quantitated fl uorescence intensity in images from three independent experiments, and we found that cells with reduced expression of either NPC1 or NPC2 accumulated ‫ف‬ 2-fold more NBD-tocopherol compared with control cells.…”
Section: Disrupted Expression Of Npc1/2 Causes Lysosomal Accumulationmentioning
confidence: 96%
See 3 more Smart Citations
“…As shown in Fig. 3A , NBD-tocopherol was efficiently taken up by the cells and concentrated in a vesicular, perinuclear compartment, reminiscent of our previous observations in human HepG2 and rat McARH-7777 hepatocytes ( 35,54 ). We quantitated fl uorescence intensity in images from three independent experiments, and we found that cells with reduced expression of either NPC1 or NPC2 accumulated ‫ف‬ 2-fold more NBD-tocopherol compared with control cells.…”
Section: Disrupted Expression Of Npc1/2 Causes Lysosomal Accumulationmentioning
confidence: 96%
“…Finally, modest supplementation with vitamin E has been reported to result in a mild improvement in motor performance in a mouse model of NPC disease ( 34 ). On the cellular level, it has been established that uptake of vitamin E occurs via endocytosis ( 35,36 ) and that a signifi cant portion of the vitamin is found in lysosomes ( 37 ). In light of these observations, we hypothesized that proper intracellular traffi cking of vitamin E (and in turn, adequate antioxidant protection) depends on timely egress from the lysosome and, therefore, on the functionality of NPC1/2.…”
Section: Binding Of Tocopherol To Purifi Ed Npc1 and Npc2mentioning
confidence: 99%
See 2 more Smart Citations
“…Antioxidants were added as either pre-formed serum complexes (25)(26)(27) or from ethanol stocks directly to the media. Both methods resulted in comparable uptake efficiencies as determined by accumulation of radioactively labeled tocopherol.…”
Section: Experimental Procedures Cell Culturementioning
confidence: 99%